2013
DOI: 10.1152/ajpendo.00533.2012
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying, mouth-to-cecum transit, and glycemic, insulin, incretin, and energy intake responses to a mixed-nutrient liquid in lean, overweight, and obese males

Abstract: Seimon RV, Brennan IM, Russo A, Little TJ, Jones KL, Standfield S, Wishart JM, Horowitz M, Feinle-Bisset C. Gastric emptying, mouth-to-cecum transit, and glycemic, insulin, incretin, and energy intake responses to a mixed-nutrient liquid in lean, overweight, and obese males. Am J Physiol Endocrinol Metab 304: E294 -E300, 2013. First published December 4, 2012; doi:10.1152/ajpendo.00533.2012.-Observations relating to the impact of obesity on gastric emptying (GE) and the secretion of gut hormones are inconsiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 45 publications
2
50
0
1
Order By: Relevance
“…In both obesity (10,11) and type 2 diabetes (12,13), postprandial GLP-1 responses have been inconsistently reported to be reduced after oral nutrients and those of GIP to be intact. However, even in health, the overall rate of gastric emptying varies from 1 to 4 kcal/min (14), and patients with long-standing type 2 diabetes frequently have accelerated or delayed gastric emptying (15).…”
mentioning
confidence: 99%
“…In both obesity (10,11) and type 2 diabetes (12,13), postprandial GLP-1 responses have been inconsistently reported to be reduced after oral nutrients and those of GIP to be intact. However, even in health, the overall rate of gastric emptying varies from 1 to 4 kcal/min (14), and patients with long-standing type 2 diabetes frequently have accelerated or delayed gastric emptying (15).…”
mentioning
confidence: 99%
“…The effect of body weight status on gastric emptying rate was studied by Seimon et al (2013) and it was found that body weight status did not influence gastric emptying. However, previous animal studies have revealed a negative association between body weight and gastric emptying rate (Bourreau et al, 2004;Kristiansen, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…While this makes the results more generalizable to a wider population, it may also mask potential different responses between lean and overweight participants. To date, only a limited number of studies have investigated the difference in appetite responses between overweight and lean participants; the results remain inconclusive (Brondel et al, 2007;Coelho et al, 2006;Lomenick et al, 2008;Seimon et al, 2013). Different study design, test foods and study populations may have partly accounted for the conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found impaired early GLP-1 secretion in response to a mixed meal or glucose in IR [30,31], others reported normal GLP-1 secretion [27]. There is however, some evidence that GLP-1 secretion is not impaired in obese compared to lean subjects [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental data suggest a link between GLP-1 and steatogenesis. Prevention or reversal of hepatic steatosis by different GLP-1 agonists including exendin-4 [11,12], liraglutide [13,14], GLP-1 (28)(29)(30)(31)(32)(33)(34)(35)(36)amide [15], and AC3174 [16] has been shown in rodents. There is evidence for the presence of GLP-1R on human hepatocytes [12,17].…”
Section: Introductionmentioning
confidence: 99%